Strength and microscale properties of bamboo fiber-reinforced concrete modified with natural rubber latex - Althoey, Fadi; Awoyera, Paul Oluwaseun; Inyama, King; Khan, Mohammad Arsalan; Mursaleen, Mohammad; Hadidi, Haitham M.; Najm, Hadee Mohammed (Frontiers in Materials, 2022)
Concrete development using alternative materials has become very important in the quest to achieve sustaina-ble developments in the built environment. However, it is critical to continually modify concrete mixtures in correcting deficiencies of fresh and long-term properties. In this study, natural rubber latex and bamboo fibre were added as constituent materials in concrete and the effects of the constituents on concrete were explored. Bamboo fibre (BF) and natural rubber latex (NRL) were added in proportions 0%, 1%, and 1.5%. The study determined the workability (slump) of fresh concrete mixes, strength, and water absorption properties of the hardened samples after curing them in water for 7, 14, and 28 days. The morphology of the concrete samples was explored using SEM-EDX equipment. The result showed that samples having 1% contents of bamboo fibre and 1% of rubber latex had the highest compressive strength among all the presented samples. Furthermore, samples containing equal but lower percentages of both bamboo and NRL had the highest compressive strength comparable to that of the control. This research showed the feasibility of combining bamboo fibre and rubber latex for an eco-friendly construction alternative approach to enhancing the performance of conventional concrete in terms of tensile strength and flexural strength properties.